Hubungan Moral Kerja dan Locus Kendali dengan Komitmen Organisasi Widyaiswara - Virsan Gustian; M.Rajab Lubis; Hasanuddin Hasanuddin (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2020)
This research aims to see the Moral relationship of work and Locus full with the commitment of Widyaiswara organization in the Center for Development and empowerment of educators and education in the field of building and electricity Medan. The hypothesis proposed is there is a Moral relationship between work and Locus control with the commitment of Widyaiswara organization in the Center of development and empowerment of educators and educational personnel in the field of building and electricity Medan. Data collection is the scale method, namely the Moral work scale, Locus of Control scale and the scale of orrganization commitment. The population is a total of 102 people. Data is analyzed using multiple regression. Results show; There is a very significant relationship between the moral work and the internal locus of control with the organizational commitment. Based on these results, it is revealed that the total donation of both the variables freely to the bound variable is 15.2%, there are 84.8% of the influence of other variables on the organizational commitments, where those other factors in this study do not Other personal factors, organizational factors (job traits, such as the identity of the task and the opportunity to interact with co-workers and others) and factors that are not from the organization, such as the absence of a job offer Much better or lower salary of the organization.Key words; Organizational Commitments, Moral Work, Locus of Control